2018
DOI: 10.1128/aem.01804-18
|View full text |Cite
|
Sign up to set email alerts
|

Amentoflavone Ameliorates Streptococcus suis-Induced Infection In Vitro and In Vivo

Abstract: Streptococcus suis, an important zoonotic pathogen, has caused considerable economic losses in the swine industry and severe public health issues worldwide. The development of a novel effective strategy for the prevention and therapy of S. suis is urgently needed. Here, amentoflavone, a natural biflavonoid compound isolated from Chinese herbs that has negligible anti-S. suis activity, was identified as a potent antagonist of suilysin (SLY)-mediated hemolysis without interfering with the expression of SLY. Amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 41 publications
3
28
1
Order By: Relevance
“…The finding that amentoflavone targets PFO activity was expected since PFO is also a member of the CDC family. Here, our data support the inhibitory effect of amentoflavone on CDC family toxins (Zhao et al, 2017;Shen et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding that amentoflavone targets PFO activity was expected since PFO is also a member of the CDC family. Here, our data support the inhibitory effect of amentoflavone on CDC family toxins (Zhao et al, 2017;Shen et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Zhao et al reported the anticytotoxin effects of amentoflavone on pneumolysin, a devastating bacterial protein toxin of Streptococcus pneumoniae and a member of the CDC family (Alouf, 2000;Zhao et al, 2017). Besides, study of Shen et al showed that amentoflavone effectively inhibited suilysin-mediated hemolysis, a member of the CDC family toxin from Streptococcus suis (Shen et al, 2018). The finding that amentoflavone targets PFO activity was expected since PFO is also a member of the CDC family.…”
Section: Discussionmentioning
confidence: 99%
“…NF‐κB is a common transcription factor that is readily activated by inflammatory factors or growth factors (Maehara, Hasegawa, & Isobe, ; Meng & Cai, ; Yi, Tang, Yang, Chen, & Fei, ). Common inflammatory factors include IL‐1β and TNF‐α, which can activate NF‐κB (Shen, Niu, Li, Deng, & Wang, ; Yao & Sun, ). When NF‐κB is inactive, it forms a complex with IkB‐α, which is distributed in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Common inflammatory factors include IL-1β and TNF-α, which can activate NF-κB (Shen, Niu, Li, Deng, & Wang, 2018;Yao & Sun, 2019). When NF-κB is inactive, it forms a complex with IkB-α, which is distributed in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The circular dichroism (CD) spectra of the β-lactamases were analyzed using a CD spectrophotometer (MOS-500; Bio-Logic, France), according to the method described in our previous study [27]. E. coli BL21 (DE3) PET-28a β-lactamases expression was induced by IPTG in the presence or absence of IAL (32 µg/mL).…”
Section: Secondary Structure Determination Of β-Lactamases By CDmentioning
confidence: 99%